Implementasi Pemungutan PPN Perdagangan Melalui Sistem Elektronik pada Kantor Pelayanan Pajak Badan dan Orang Asing - Setiawan, Ade; Sari, Nurmita (Journal of Business Administration Economics & Entrepreneurship, 2023)
Internet penetration in Indonesia makes the digital economy rapidly developed, and this progress makes a significant change in people's consumption pattern to be a contactless. This consumption pattern enable them to purchase digital services from abroad. The Directorate General of Taxes as the tax authority in Indonesia must be able to take advantage of this momentum to increase state revenue through expanding the tax base through the collection of Value Added Tax (VAT) in Trade through Electronic Systems (PMSE) on Intangible Taxable Goods and Services originating from abroad. The purpose of this study is to understand how the Implementation of PMSE VAT Collection at Permanent Establishment and Expatriates Tax Office, The researcher use Descriptive Qualitative and data collection techniques through Interviews and Documents Review Methods. Based on research conducted, the results of the Implementation of PMSE VAT Collection at Permanent Establishment and Expatriates Tax Office as follows are the implementation of PMSE VAT Collection starting from appointment as VAT Collector to depositing the VAT collection has been running well according to the 3 rules that govern it : Peraturan Menteri Keuangan No 48/PMK.03/2020 as amended by Peraturan Menteri Keuangan No 60/PMK.03/2022, Peraturan Jenderal Pajak No PER-12/PJ/2020 and also the Implementation Instructions contained in the Circular Letter of the Director General of Taxes number SE-44/PJ/2020. The implementation of PMSE VAT collection on tax revenues at KPP Badan dan Orang Asing conducted PMSE VAT collection plays a major role in revenue from KPP Corporate and Foreign Persons. This can be seen from the percentage of the role of VAT PMSE collection on revenue from KPP Badan dan Orang Asing. which continues to increase from 18.88% at the beginning of the PMSE VAT collection regulations being implemented in 2020, to 49.45% in 2021 and again increasing in 2022 to 54.79% of the total KPP revenues of Foreign Entities and Persons Keywords: Value Added Tax (VAT) in Trade through Electronic Systems (PMSE), Electronic Transaction, Foreign Enterprise and Individual Tax Office Directorate General of Taxes